2016
DOI: 10.1097/mib.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Treatment Induces Long-lasting Changes in the Fecal Microbiota that Protect Against Colitis

Abstract: Background The interplay between host genetics, immunity, and microbiota is central to the pathogenesis of inflammatory bowel disease (IBD). Previous population-based studies suggested a link between antibiotic use and increased IBD risk, but the mechanisms are unknown. The purpose of this study was to determine the long-term effects of antibiotic administration on microbiota composition, innate immunity, and susceptibility to colitis, as well as the mechanism by which antibiotics alter host colitogenicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 67 publications
5
15
0
Order By: Relevance
“…The colitis severity was evaluated through body weight loss, disease activity index (DAI) scores, colon lengths and histopathological scores. ABX treatment, which is widely used to clear normal intestinal bacteria, greatly reduced mice susceptibility to DSS treatment as reported previously [21] (Fig. S2A to D, additional le 2).…”
Section: Mice Susceptibility To Dss-induced Colitis Is In Uenced By Dsupporting
confidence: 84%
“…The colitis severity was evaluated through body weight loss, disease activity index (DAI) scores, colon lengths and histopathological scores. ABX treatment, which is widely used to clear normal intestinal bacteria, greatly reduced mice susceptibility to DSS treatment as reported previously [21] (Fig. S2A to D, additional le 2).…”
Section: Mice Susceptibility To Dss-induced Colitis Is In Uenced By Dsupporting
confidence: 84%
“…This may indicate that the effect of lowering or increasing the microbial burden in the gut influences the production of granulocytes in the BM as well as their recruitment into circulation. This is supported by the finding that neonatal mice born to ABX‐treated dams exhibit reduced granulocyte numbers in BM and blood and reduced GMPs in BM . In a previous study, we found that recolonizing germ‐free adult mice with a complete SPF microbiota fully restored mature circulating monocytes and neutrophils, while colonization with a single strain ( L. acidophilus or E. coli ) was not able to do so, probably due to inadequate number and stimulation .…”
Section: Discussionsupporting
confidence: 52%
“…A comparable reduction in granulocytes/neutrophils is found in BM and circulation in germ‐free neonatal mice and in pups born to antibiotic‐treated dams . Furthermore, ABX treatment of adult mice decreases the number of circulating T cells, and ceasing the treatment gradually restores CD4 + and CD8 + T cells numbers . This gradual lymphocyte restoration coincides with an altered and less diverse microbiota many weeks after the cessation of ABX treatment .…”
Section: Introductionmentioning
confidence: 65%
“…Antibiotic pretreated mice were shown to attenuate intestinal chemically induced inflammation [73, 74]. In patients with IBD, a Helicobacter , Campylobacter , and Enterococcus species-dominant microbial profile was reported [75, 76].…”
Section: The Microbial Gut-brain Axismentioning
confidence: 99%